Appearance, discrimination and the media : portraying facial disfigurement fairly in the news - Garrisi, Diana (CAMRI policy briefs ;, 2018)
"The portrayal of disfigurement in the UK media must change. This policy brief is based on recent research that found a general negative and sensationalised attitude towards disfigurement in the media. Disfigurement is a condition that can affect anyone at any time in life regardless their social or demographic background due to accidents or health conditions or be congenital. In the UK, one in 111 people have facial disfigurements. In order to improve the ways in which media portray disfigurement, this policy brief argues that media should move away from sensationalised coverage on disfigurement and focus instead on the lived experiences of individuals with this condition. It recommends strengthening diversity-oriented editorial practices and training as well as media literacy education. In addition, it addresses the lack of guidelines on the portrayal of disfigurement and urges regulatory bodies to be more efficient in handling complaints."